MANIFESTATION OF INTENSITY IN THE SYNTACTIC METHOD - Tukhtayeva Dilafruz Ashurovna, (Ustozlar uchun, 2025)
Intensity is a sign of the first stage of parametric quantities, acting as a direct characteristic of things-objects. Intensity is manifested not only as a measure of expressiveness (mainly associated with the introduction of various intensifiers into the text), but also as its component. If any feature in a sentence is intensified, then the general sentence may acquire expressiveness. Intensity, as a measure of quantity, has its own specific methods of manifestation.